Cardiac rehabilitation. Current status and future directions. - Gattiker, H. (1992)
Comprehensive cardiac rehabilitation is more than exercise training for patients with coronary artery disease and now includes all aspects of secondary prevention. Exercise training is individually prescribed based on clinical status and therapeutic goals. Smoking cessation and abstinence and the treatment of hypercholesterolemia are integral to the rehabilitation process. Education and counseling are important adjuncts to treatment, especially soon after a coronary event. Vocational rehabilitation can be included simply and effectively in the rehabilitation process. Efficient and cost-effective cardiac rehabilitation is tailored to a patient's medical condition, risk factor evaluation, and vocational status. The future of cardiac rehabilitation will be linked to the success of training nonphysician health professionals to provide preventive services.